Ansatz of leptonic mixing: The alliance of bi-maximal mixing with a single-angle rotation - Siyeon, Kim (Journal of the Korean Physical Society, 2014)
We introduce an ansatz of the Pontecorvo-Maki-Nakagawa-Sakata (PMNS) matrix that consists of specific types of transformations. Bi-maximal mixing is taken for the neutrino masses while a single-angle rotation in the 1–2 block is taken for the charged lepton masses. Motivated by the implications of the recent results on neutrino oscillations, θ 23 in the first octant and non-zero θ 13 are predicted by the ansatz. Three physical mixing angles are expressed in terms of a single variable, the 1–2 angle of charged leptons, so that a simple relation among the angles has been obtained: tan θ 13 = (sin θ 23 − sin θ 12 ). Finally a model of the inverted hierarchy that can produce the given ansatz is proposed.